Odpowiedzi

2009-12-20T17:10:07+01:00
A)
x = 3y
8 y = 16
y = 2
x = 6

b)
y = 2x - 1
x = 0
y = -1
1 5 1
2009-12-20T17:09:53+01:00
A)
(x=3y
(2x+2y=16

x=3y
2(3y)+2y=16

x=3y
8y=16

x=3y
y=2

x=6
y=2


b)
(x+2y=-2
(2x-y=1

x=-2-2y
2(-2-2y)-y=1

x=-2-2y
-4-4y-y=1

x=-2-2y
-5y = 5

x=-2-2y
y=-1

x=-2+2 = 0
y=-1
1 5 1
2009-12-20T17:14:19+01:00
A)
{x=3y (1)
{2x+2y=16 (2)
(1) wstawiam do (2):
{x=3y
{2*3y+2y=16
{x=3y
{6y+2y=16
{x=3y
{8y=16 /:8
{x=3y
{y=2 (3)
(3) wstawiam do (1):
{y=2
{x=3*2
{y=2
{x=6
UKŁAD OZNACZONY (6;2)

b)
{x+2y=-2
{2x-y=1
{x=-2y-2 (1)
{2x-y=1 (2)
(1) wstawiam do (2):
{x=-2y-2
{2*(-2y-2)-y=1
{x=-2y-2
{-4y-4-y=1
{x=-2y-2
{-5y=5 /:(-5)
{x=-2y-2
{y=-1 (3)
(3) wstawiam do (1):
{y=-1
{x=-2*(-1)-2
{y=-1
{x=0
UKŁAD OZNACZONY (0;-1)

1 5 1